Marshall and Labour Demand in Russia: Going Back to Basics - Jozef Konings; Hartmut Lehmann (Institute for the Study of Labor (IZA), 2001)
Using a unique enterprise-level data set, which covers the regions Moscow City, Chelyabinsk, Krasnoyarsk and Chuvashia and the three sectors manufacturing and mining, construction and trade and distribution, we estimate Russian labour demand equations for the year 1997. The most important conclusion that can be drawn is that labour demand is inelastic in international perspective if we estimate a labour demand equation for all regions and all sectors combined. So, Russian MLEs well into the transition still exhibit peculiar behaviour as far as wage employment trade-offs are concerned. We try to relate this inelastic labour demand to basic neoclassical theory by testing Marshall?s rules of derived demand. Our results show that testing these rules seems a promising avenue for establishing some of the driving forces, which are behind labour demand in Russia.
Keywords: P20; J23; 330; Transition economics; demand for labour; Arbeitsnachfrage; Mikroökonomische Konsumfunktion; Übergangswirtschaft; Elastizität; Schätzung; Russland